2013
DOI: 10.1021/bi3016235
|View full text |Cite
|
Sign up to set email alerts
|

Relative Timing of Hydrogen and Proton Transfers in the Reaction of Flavin Oxidation Catalyzed by Choline Oxidase

Abstract: The oxidation of the reduced flavin in choline oxidase was investigated with pH, solvent viscosity, and kinetic isotope effects (KIEs) in steady-state kinetics and time-resolved absorbance spectroscopy of the oxidative half-reaction in a stopped-flow spectrophotometer. Both the effects of isotopic substitution on the KIEs and the multiple KIEs suggest a mechanism for flavin oxidation in which the H atom from the reduced flavin and a H(+) from the solvent or a solvent exchangeable site are transferred in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…H/D exchange at N5-FMN red was documented but did not explain the small KIE. A similar primary KIE of only 2 was observed for complex I and was attributed to hydride transfer’s being only partially rate-determining (Birrell and Hirst, 2013) and a primary KIE of ~1.5 was also observed in the flavin-oxidizing half-reaction of choline oxidase (Gannavaram and Gadda, 2013). More detailed studies are required to establish whether the chemical step is solely responsible for our primary KIE, however this interpretation is strengthened by the similarity of the KIEs on k cat and on k cat /K M .…”
Section: Discussionsupporting
confidence: 54%
“…H/D exchange at N5-FMN red was documented but did not explain the small KIE. A similar primary KIE of only 2 was observed for complex I and was attributed to hydride transfer’s being only partially rate-determining (Birrell and Hirst, 2013) and a primary KIE of ~1.5 was also observed in the flavin-oxidizing half-reaction of choline oxidase (Gannavaram and Gadda, 2013). More detailed studies are required to establish whether the chemical step is solely responsible for our primary KIE, however this interpretation is strengthened by the similarity of the KIEs on k cat and on k cat /K M .…”
Section: Discussionsupporting
confidence: 54%
“…29 In contrast, the flavooxidase choline oxidase proved to transfer both the H and H + to O 2 in a concerted manner, in the same chemical step, as arisen from the studies of multiple isotope effects on k cat /K ox . 36…”
Section: Agingmentioning
confidence: 99%
“…To the best of our knowledge, the mechanism of the oxidative half-reaction was investigated in detail in three oxidases, namely pyranose 2-oxidase, 30,31 choline oxidase 34 and arylalcohol oxidase. 35 It was found that their mechanisms con- cerning the sequence and relative energetics of the elementary steps are different.…”
Section: Introductionmentioning
confidence: 99%